Cause-of-death ascertainment for deaths that occur outside hospitals in Thailand: application of verbal autopsy methods - Pattaraarchachai Junya; Adair Timothy; Rao Chalapati; Polprasert Warangkana; Porapakkham Yawarat; Lopez Alan D (BMC, 2010)
Abstract Background Ascertainment of cause for deaths that occur in the absence of medical attention is a significant problem in many countries, including Thailand, where more than 50% of such deaths are registered with ill-defined causes. Routine implementation of standardized, rigorous verbal autopsy methods is a potential solution. This paper reports findings from field research conducted to develop, test, and validate the use of verbal autopsy (VA) methods in Thailand. Methods International verbal autopsy methods were first adapted to the Thai context and then implemented to ascertain causes of death for a nationally representative sample of 11,984 deaths that occurred in Thailand in 2005. Causes of death were derived from completed VA questionnaires by physicians trained in ICD-based cause-of-death certification. VA diagnoses were validated in the sample of hospital deaths for which reference diagnoses were available from medical record review. Validated study findings were used to adjust VA-based causes of death derived for deaths in the study sample that had occurred outside hospitals. Results were used to estimate cause-specific mortality patterns for deaths outside hospitals in Thailand in 2005. Results VA-based causes of death were derived for 6,328 out of 7,340 deaths in the study sample that had occurred outside hospitals, constituting the verification arm of the study. The use of VA resulted in large-scale reassignment of deaths from ill-defined categories to specific causes of death. The validation study identified that VA tends to overdiagnose important causes such as diabetes, liver cancer, and tuberculosis, while undercounting deaths from HIV/AIDS, liver diseases, genitourinary (essential renal), and digestive system disorders. Conclusions The use of standard VA methods adapted to Thailand enabled a plausible assessment of cause-specific mortality patterns and a substantial reduction of ill-defined diagnoses. Validation studies enhance the utility of findings from the application of verbal autopsy. Regular implementation of VA in Thailand could accelerate development of the quality and utility of vital registration data for deaths outside hospitals.